Laparoscopic removal of foreign body- a case report - Jha, Santosh; Dangal, Ganesh (Journal of Chitwan Medical College, 2021)
Iatrogenic disease is defined as an illness caused by diagnostic procedures or treatment given by health care professionals. Iatrogenic foreign bodies are not uncommon in the medical literature. It is primarily as a result of human error and is reported rarely due to medico legal implications it carries. The varieties of foreign bodies like sponge, gauze, surgical instruments have been retrieved. Retained surgical sponge or gauze after operation is called Gossypiboma. It has varied and vague presentation and is also difficult to detect by radiological investigations.